Pengembangan Materi Pembelajaran IPS untuk Kelas Awal dan Kelas Lanjut dalam Kurikulum Sekolah Dasar - Syafruddin Syafruddin; Miftatul Qahairatul; Nur Rabiah; Ela Ayuspita; Nursakinah Nursakinah (Syntax Corporation Indonesia, 2024)
This research aims to develop Social Sciences (IPS) learning materials that suit the needs of students in early grades (1, 2, and 3) and advanced grades (4, 5, and 6) in the Elementary School Curriculum. This learning material development approach uses a competency-based approach and refers to the principles of fun and student-centered learning. The methods used are literature study, observation, and consultation with education experts. Early grades require a more visual and playful approach to social studies learning. Therefore, learning materials for early grades are designed taking these needs into account. For example, material about the surrounding environment is presented through pictures, role plays and short stories that are relevant to children's daily lives. Meanwhile, advanced classes require a more analytical and contextual approach in learning social studies. Learning materials for advanced classes are prepared taking into account students' cognitive and social development. For example, material on history is presented through case studies, group discussions, and simple research projects that allow students to develop analysis and synthesis skills. It is hoped that the results of the development of social studies learning materials will increase students' interest and understanding of social studies materials and help teachers present learning materials that are interesting and relevant to students' needs.